A Strategy Tripod Perspective on Knowledge Creation Capability. (26th August 2015) - Su, Zhongfeng; Peng, Mike W.; Xie, En
Abstract : Drawing on the strategy tripod perspective, in this study we examine how the performance effect of knowledge creation capability is contingent on key industrial and institutional variables. We find that technological turbulence, competitive intensity and government support all positively moderate the relationship between knowledge creation capability and firm performance, while dysfunctional competition has a negative moderating impact. This study provides a more fine‐grained analysis on the performance implications of knowledge creation capability. Moreover, it represents one of the first attempts to empirically test the interactive effects of the three legs of the strategy tripod (the industry‐based, resource‐based and institution‐based views) in one study and supports the importance of integrating the three legs to better understand the complex phenomenon.